Gamification for Internet Gaming Disorder Prevention: Evaluation of a Wise IT-Use (WIT) Program for Hong Kong Primary Students - Chau, Chor-lam; Tsui, Yvonne Yin-yau; Cheng, Cecilia (Frontiers in Psychology, 2019)
Background Internet gaming disorder and risky online behavior (e.g., cyberbullying, exposure to online violent content) have emerged as serious problems in the present digital era. Their prevalence rates range from 4% to 40% across the globe, with Asia being one of the hardest-hit regions. To address these pressing problems, our team has designed a universal prevention program, the Wise IT-use (WIT) program, which (a) enhances students’ awareness of Internet gaming disorder and an array of common risky online behaviors and (b) equips them with sufficient knowledge to handle such problems. The WIT program is based on gamification principles and flow theory to enhance users’ motivation and learning experience. This program evaluation study was conducted to assess the new program’s efficacy in mitigating Internet gaming disorder symptoms and risky online behavior as well as bolstering mental health. Methods The participants were 248 students (56% boys; Mage = 10.16, SD = .97; age range = 7–13) from four primary schools in various regions of Hong Kong. They completed validated self-report questionnaires one month before and two months after participating in the WIT program to evaluate potential changes in their Internet gaming disorder symptoms, the frequency of their display of risky online behaviors, and their mental health ratings across the period. Results The results revealed the WIT program to reduce both the symptoms of Internet gaming disorder and the proportion of students at risk of the disorder (ps < .0001). After the students had taken part in the program, their lower frequencies of such symptoms and risky online behaviors were found to be related to higher levels of positive affect (ps < .03) and lower levels of negative affect (ps < .004). Conclusions The present study provides evidence indicating that Internet gaming disorder and risky online behavior are both detrimental to the mental health of Hong Kong primary students. More importantly, the findings show our newly developed WIT program to successfully mitigate the symptoms of such disorder and enhance psychological well-being over time. The implications of these findings for the program’s broader impact on the society and culture are discussed.